Diagnosing organizational effectiveness in the tourism sector of Zanzibar,Diagnosing organisational effectiveness in the tourism sector of Zanzibar - Raja, Sanjay Kanji (Rhodes University, Faculty of Commerce, Rhodes Business School, 2012)
The tourism sector in Zanzibar Tanzania has emerged strongly in the past 15 years, helping the development of other Industries that support it. As a result, Industries such as telecommunication, IT, transport and hospitality have also emerged recently. It is, however, speculated that organizations in the tourism sector in Zanzibar generally lack the effective performance that is required of them to compete in the contemporary complex and turbulent market environment. This research thus set out to explore and diagnose the organizational effectiveness of the accommodation units of the tourism sector in Zanzibar. The research had specific objectives of diagnosing and finding the gap between the current and the optimal organizational performance in two particular units of accommodation as well as determining the factors affecting organizational performance in these units. The study furthermore set out to recommend implementation of suitable intervention activities to improve organizational performance in the units analyzed. In order to achieve the above objectives the research deployed an action research strategy with the Weisbord's six box model as a framework to diagnose two five star grade accommodation units in Zanzibar. A qualitative method was used to collect data. Key findings of the research are briefly presented below: - The service output of the accommodation units analyzed was not very consistent and fell short of the expectation of their customers. This showed a gap in terms of the organizations' performance. - Factors affecting organizational effectiveness were found to be mainly in the Purpose and Rewards functions of the organizations. - The specific areas in the Purpose function that appeared to have substantial problems were: -- Goals of the organization were not clearly stated -- Employees did not understand the purpose of the organization -- Employees were not involved in deciding their work unit goals -- Employees were not in agreement with the goals of their work units. -- Employees did not understand priorities of the organization The specific areas in the Reward function that appeared to have substantial problems were: -- The pay scale and benefits of the organization did not treat employees equitably. -- Employees felt that the salary they received was not commensurate with the jobs they performed. -- Not all tasks to be accomplished were associated with incentives. Following the diagnostics findings above, the research suggested the following intervention activities that could possibly help to address the above mentioned problems: - A Management by Objectives (MBO) process was suggested to redress the problems indicated in the Purpose function. This would help to set clearly agreed goals at all levels of the organizations. Employees and resources would then be directed towards achieving these goals that would enable the organizations to perform more effectively. - Revision of the current reward system was suggested to redress the problems indicated in the Reward function. The reward system should be implemented in a manner that creates a feeling of both internal as well as external (market) equity among employees. Furthermore, rewards should be linked to performance in order to direct behaviour and motivation among employees. The performance based reward system can also help to achieve the MBO process proposed above since rewards will be designated for achievement of individual, departmental and finally organizational objectives, thus increasing organizational effectiveness.
Keywords: Organizational effectiveness -- Zanzibar; Management by objectives -- Zanzibar; Tourism -- Zanzibar; Tourism -- Management -- Zanzibar; Job satisfaction -- Zanzibar; Employee motivation -- Zanzibar